Uncoupling of glycolysis from glucose oxidation accompanies the development of heart failure with preserved ejection fraction - Natasha Fillmore; Jody L. Levasseur; Arata Fukushima; Cory S. Wagg; Wei Wang; Jason R. B. Dyck; Gary D. Lopaschuk (BMC, 2018)
Abstract Background Alterations in cardiac energy metabolism contribute to the development and severity of heart failure (HF). In severe HF, overall mitochondrial oxidative metabolism is significantly decreased resulting in a reduced energy reserve. However, despite the high prevalence of HF with preserved ejection fraction (HFpEF) in our society, it is not clear what changes in cardiac energy metabolism occur in HFpEF, and whether alterations in energy metabolism contribute to the development of contractile dysfunction. Methods We directly assessed overall energy metabolism during the development of HFpEF in Dahl salt-sensitive rats fed a high salt diet (HSD) for 3, 6 and 9 weeks. Results Over the course of 9 weeks, the HSD caused a progressive decrease in diastolic function (assessed by echocardiography assessment of E'/A'). This was accompanied by a progressive increase in cardiac glycolysis rates (assessed in isolated working hearts obtained at 3, 6, and 9 weeks of HSD). In contrast, the subsequent oxidation of pyruvate from glycolysis (glucose oxidation) was not altered, resulting in an uncoupling of glucose metabolism and a significant increase in proton production. Increased glucose transporter (GLUT)1 expression accompanied this elevation in glycolysis. Decreases in cardiac fatty acid oxidation and overall adenosine triphosphate (ATP) production rates were not observed in early HF, but both significantly decreased as HF progressed to HF with reduced EF (i.e. 9 weeks of HSD). Conclusions Overall, we show that increased glycolysis is the earliest energy metabolic change that occurs during HFpEF development. The resultant increased proton production from uncoupling of glycolysis and glucose oxidation may contribute to the development of HFpEF.